Default in Tuberculosis Treatment among Women Registered in DOTS Center of Taplejung District, Nepal: A Descriptive Study (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Default is one of the unfavourable outcomes for patients on DOTS and represents an important challenge for the control program. Therefore, this study was designed to assess default in tuberculosis (TB) treatment among women registered in DOTS center at Taplejung District of Nepal.MATERIALS AND METHODS: A descriptive cross-sectional study was conducted at Taplejung district of Nepal in thethe year 2016. Records of TB patients from all DOTS centre for one year were obtained and treatment default cases for women were identified. Face to face interview was conducted by using semi-structured questionnaire to collect data from the patients. The data were entered and analyzed in MS Excel software.RESULTS: Out of total 30 female TB patients, 72.0% of respondents belonged to the age group of 15-49 years where as 73.3% of the respondents were Kirat and from Dalit caste ethnicity. Less than half of the respondents (48.0%) thought, feeling better after medication, was the reason for default TB. A second major cause for default in tuberculosis treatment was distance to reach DOTS center (12.0%) and lack of food at home (10.0%). Likewise, few respondents said lack of family support (6.7%), thinking about side effects (6.7%), medicine not working (3.3%) and stigma (6.7%) were the reasons for the default in tuberculosis treatment.CONCLUSIONS: Majority of the respondents left treatment because they felt better after medication. A second major reason for default in TB treatment was distance to reach DOTS center. The findings may be helpful in planning modifications in DOTS program of Nepal.